Where Do I Fit? A 'Check-Up' on the Role of the Fat Researcher in Health Care Spaces. Issue 2 (3rd May 2020) - Ioannoni, Kelsey
ABSTRACT: Feminist research must provide the reader with 'accountable knowledge, ' allowing the reader to critically assess the context of the research and the location of the researcher. As a sociologist, I conduct research on the experiences of fat women within the Canadian health care system. My experiences as a fat woman with frequent interactions with health care cannot be separated out from the context in which my research is conducted, as these experiences are the starting point of my interest in examining institutionalized fatphobia in medicine. This paper explores the role of the fat researcher, specifically myself, in fat studies research. As a fat woman I am both hypervisible and hyper(in)visible, and the hypervisibility of my fatness is inescapable. This visibility is impossible to hide or distance myself from and implicates me in the research process. Using Letherby and Stanley's work on the auto/biographical 'I, ' I unpack the implications of my experience with health care professionals in my own research on the way in which fatness acts as a barrier to accessing health care.